1964
DOI: 10.1152/jappl.1964.19.4.583
|View full text |Cite
|
Sign up to set email alerts
|

Physiological reactions of Caucasian and Bantu males in acute exposure to cold

Abstract: Eleven men per sample of Caucasian and Bantu males were exposed for 2 hr in a climatic chamber at various air temperatures ranging from 5 to 27 C, and a wind velocity of 80–100 ft/min. When expressed per square meter surface area the metabolism of the Bantu was greater in the range above 18 C and below 6 C. Average skin temperatures were similar for both groups, but between 27 and 17 C the toe and finger temperatures of the Caucasians were significantly higher than that of the Bantu—the difference at 27 C bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1972
1972
2009
2009

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The experimental data represent averages for semi-nude, seated individuals after 1 h exposure to a range of environment temperatures between 5 and 50 1C, obtained for 44 persons by Wyndham et al [33] and for 86 individuals by Werner and Reents [34]. A reasonable agreement between them is observed.…”
Section: Article In Presssupporting
confidence: 54%
“…The experimental data represent averages for semi-nude, seated individuals after 1 h exposure to a range of environment temperatures between 5 and 50 1C, obtained for 44 persons by Wyndham et al [33] and for 86 individuals by Werner and Reents [34]. A reasonable agreement between them is observed.…”
Section: Article In Presssupporting
confidence: 54%
“…17. The experimental data represent averages (±SD) for 44 (Wyndham et al 1964) (Fig. 17A) and three (Gagge et al 1967;Hardy and Stolwijk 1966) (Fig.…”
Section: Fig 11mentioning
confidence: 99%
“…The changes in skin temperature (Tsk) and hand blood flow occurring in response to cold exposure have been interpreted as indicators of cold acclimatization (Budd 1964;Budd and Warhaft 1966). The studies conducted by Wyndham et al (1964aWyndham et al ( , b, 1968 demonstrated a fall in mean Tsk during men's stay in Antarctica. This is a typical response of non-acclimatized adult men subjected to cold (Budd 1964); however, after accliCorrespondence to: U. Sachdeva matization in Antarctica the peripheral blood flow was increased in men after 12 months of stay in Antarctica (Bodey 1978).…”
Section: Introductionmentioning
confidence: 99%